2009
DOI: 10.5688/aj7306101
|View full text |Cite
|
Sign up to set email alerts
|

A Computer-based Module for Prescribing Error Instruction

Abstract: Objective. To evaluate an instructional module's effectiveness at changing third-year doctor of pharmacy (PharmD) students' ability to identify and correct prescribing errors. Design. Students were randomized into 2 groups. Using a computer-based module, group 1 completed worksheet A, watched a presentation on medication errors, and then completed worksheets B and C. Group 2 completed worksheets A and B, watched the presentation, and then completed worksheet C. Assessment. Both groups scored a median 50% on wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…The logistical and financial burden of creating additional checking stations may be minimized with the use of product pictures or online programs. 2,14 Online programs could additionally be used to supplement scheduled curricular activities by providing extra practice exercises for students to complete on their own time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The logistical and financial burden of creating additional checking stations may be minimized with the use of product pictures or online programs. 2,14 Online programs could additionally be used to supplement scheduled curricular activities by providing extra practice exercises for students to complete on their own time.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Furthermore, students' awareness of their role in preventing medication errors increased as a result of taking the medication safety laboratory sessions. 13 Computer-based modules 2,3,14 and "mock pharmacy" 12 techniques have also been identified as modes to further enhance active learning.…”
Section: Introductionmentioning
confidence: 99%
“…11 Computer-based modules proved effective in teaching pharmacy students to identify and correct prescription errors. 12 Use of computer-assisted medicinal chemistry case study modules helped students better understand how to evaluate structure activity relationship findings in relation to desired therapeutic outcomes and addressing therapeutic problems in a clinical setting. 13 Another study found that using Web-based prescription simulations that depicted different scenarios relating to pharmacy practice in a hospital setting or community setting assisted the learning process for students in a practice skills laboratory course.…”
Section: Introductionmentioning
confidence: 99%
“…An example of reporting an effect size can be seen in a study evaluating a prescribing error module. 36 In this study, the researchers compared 2 groups on 3 worksheets and noted a large effect of 0.85 associated with a significant difference on 1 of the worksheets.…”
Section: Effect Sizementioning
confidence: 99%